The causality between gut microbiome and chronic regional pain: a Mendelian randomization analysis - Xiao, Qing-Ao; Qin, Lei; Yu, Jing; Hu, Yin-Tao; Ai, Lin-Feng; Wang, De-Cheng; Xia, Xuan; Zhang, Xiao-Lin (Frontiers in Microbiology, 2024)
Background Numerous investigations had underscored causal effect between chronic pain (CP) and gut microbiota, jointly contributing to the onset and development of widespread chronic pain. Nonetheless, there was still unknown about causal effect between gut microbiota and chronic regional pain (CRP). Methods Genome-wide association study (GWAS) summary data of gut microbial taxa (Mibiogen Consortium: 211 microbiotas and the Dutch Microbiome Project: 207 microbiotas) and eight types of chronic regional pain were used to reveal the causal effect between the persistent pain in specific region of body and gut microbiota. A two-sample bidirectional Mendelian randomization (MR) design was used. In order to ensure the accuracy of results, multiple sensitivity analyses were employed. Results This study uncovered significant causal associations between six gut microbial taxa and three types of CRP (Forward: Genus Parabacteroides for general pain; Class Bacteroidia, Order Bacteroidales, and Phylum Bacteroidetes for back pain. Reverse: knee pain for Genus Howardella and Order Coriobacteriales) by forward and reverse MR analysis. These findings had been verified by rigorous Bonferroni correction. Furthermore, this research identified 19 microbial taxa that exhibited potential correlations with four types of CRP. There are no significant or potential gut microbiotas which were associated with other types of CRP, including fascial pain, stomach or abdominal pain and hip pain. Conclusions This two-sample bi-directional MR analysis unveiled the causality between gut microbial taxa and eight chronic regional pain conditions. The findings reveal the interplay between CRP and 6 gut microbiotas, while also delineating 19 potential specific microbial taxa corresponding to diverse locations of persistent pain.